Transformation Culture Islamic School through Internalization of Obedience Values in Local Tradition Nggusu Waru - Abu Bakar (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STIT Sunan Giri Bima, 2025)
Study This aim analyze implementation mark obedience in the character of “ Nggusu Waru” as well as his contribution to formation identity and culture school at Insan Kamil IT Middle School, Bima City. Background study This based on the importance education character based wisdom local as response to challenge globalization and crisis moral identity of participants education . Research use approach qualitative with design studies case . Data collected through semi- structured interviews , observation participatory , and study documentation , with informant head selected schools , teachers, and students in a way purposive . Data analysis was carried out in a way interactive through data reduction , data presentation , and data extraction conclusion with technique triangulation For ensure data validity . Research results show that mark obedience internalized through habituation structured , teacher role models , and integration in activity academic and religious like discipline presence , prayer congregation , and responsibility answer academic . Implementation This impact on increasing discipline , responsibility answer , and strengthening mark social and religious students . In addition to forming character individual , the value of “ Nggusu Waru” contributes to construction culture a school that is religious and rooted in identity Bima local research This conclude that education character based wisdom local own role strategic in build identity institutional Islamic schools in general contextual and sustainable , although his success still influenced by factors family and environment social .